An air-stable half-sandwich RuII complex as an efficient catalyst for [3+2] annulation of 2-arylcyclo-2-enones with alkynes. Issue 25 (22nd January 2016) - Zhao, Yinsong; He, Zhen; Li, Shiqing; Tang, Junbin; Gao, Ge; Lan, Jingbo; You, Jingsong
Abstract : An air-stable half-sandwich Ru II complex, [Ru( p -cymene)(MeCN)3 ](SbF6)2, catalyzed a [3+2] annulation reaction of 2-arylcyclo-2-enones with alkynes via C(sp 2 )–H/alkene functionalization to construct synthetically challenging spiro carbocyclic indenes bearing a quaternary carbon. Abstract : An air-stable half-sandwich ruthenium II complex, [Ru( p -cymene)(MeCN)3 ](SbF6 )2, was synthesized and characterized. It exhibited unique catalytic ability in a [3+2] annulation reaction of 2-arylcyclo-2-enones with internal alkynes via C(sp 2 )–H/alkene functionalization, which offered a rapid and atom-economical methodology to construct various synthetically challenging spiro carbocyclic indenes bearing a quaternary carbon.